PENGARUH MEDIA VIDEO BUDAYA LOKAL TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP - Nurnanengsi Nurnanengsi; Nurhusna Nurhusna (Universitas Negeri Makassar, 2020)
The Influence of Local Culture Video Media on the Ability to Write Descriptive Texts of Class VII Junior High School Students. This study aims to determine the effect of local cultural video media on the ability to write descriptive texts of seventh grade students of SMP Negeri 3 Bissappu, Bantaeng Regency. The research method used in this research is pre-experimental design with One Group Pretest-Postest Design research design. The data collection technique is a test which is divided into pretest and postest. Data analysis used descriptive statistics and inferential statistics. The results showed that there was an influence between local cultural video media on the ability to write descriptive text for seventh grade students of SMP Negeri 3 Bissappu, Bantaeng Regency.